On the invariance of the Stimulant Craving Questionnaire (STCQ) across cocaine and methamphetamine users. (March 2015) - Northrup, Thomas F.; Green, Charles; Walker, Robrina; Greer, Tracy L.; Trivedi, Madhukar H.
Abstract: Background: The rapid rise in the number of methamphetamine users, relative to cocaine users, has brought the number of each to nearly equal levels, making research on similarities and differences across these groups a needed area of exploration. Craving is postulated to play a significant role in relapse for both user types, yet group differences on observed scale scores have been reported without first assessing the prerequisite measurement equivalence (invariance) of the items, which is essential for meaningful group comparisons. Methods/design: Baseline data from stimulant users in residential treatment (N = 301; n = 177 cocaine; n = 124 methamphetamine) were used to assess the measurement invariance of the 10-item Stimulant Craving Questionnaire (STCQ), which was adapted from a cocaine-specific measure. Results: The unifactorial STCQ demonstrated measurement invariance across cocaine and methamphetamine users for factor loadings (metric), common residual covariances between item pairs, and item intercepts (scalar), as determined by fit indices (RMSEA < 0.05; CFI & TLI > 0.95; SRMR < 0.10). The latent mean, as well as 5 (out of 10) item means and the overall composite scale score, was significantly greater for methamphetamine users compared to cocaine users. Discussion: Results indicate the STCQ is an invariant tool for the assessment of stimulant craving across the two most prevalent user types. Methamphetamine users had significantly higher levels of observed and latent craving than cocaine users, demonstrating a potentially meaningful difference in craving between users of these two stimulants. Future research will determine if treatments and statistical models need to account for craving variations across methamphetamine and cocaine users. Highlights: An invariant measure of craving is needed across methamphetamine and cocaine users. The Stimulant Craving Questionnaire demonstrated invariance across both user types. During residential treatment, methamphetamine users had greater latent craving. Future research will determine the clinical utility of these craving differences.